2010
DOI: 10.1097/rhu.0b013e3181df822d
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Disease and Pulmonary Hypertension Responsive to Low-Dose Ultraviolet A1 Irradiation in Lupus

Abstract: In three placebo-controlled, double-blind studies, low-dose, full body UVA1 irradiation administered 2-3 times a week had a remedial action in patients with systemic lupus erythematosus (SLE) [1][2][3] . SLE Activity Measure (SLAM) and SLE Disease Activity Index (SLEDAI) scores decreased significantly. The therapy mitigated fatigue, joint pain, rashes, cognitive dysfunction, and photosensitivity within days to weeks, and over the years appeared to maintain these gains 4 . In only one of these studies was an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…UVA-1 radiation in lupus-prone MRL-lpr mice also prevented development of CLE-like skin lesions (45). Based on these findings, UVA-1 was tested in SLE patients in varying dosing regimens in case report, open-label and randomized control trial settings ( Table 2) (37)(38)(39)(40)(41)(46)(47)(48)(49)(50). In these trials, UVA-1-treated patients demonstrated decreased systemic symptoms and disease activity scores (e.g.…”
Section: Uva-1 Therapy For Lupus Patientsmentioning
confidence: 99%
“…UVA-1 radiation in lupus-prone MRL-lpr mice also prevented development of CLE-like skin lesions (45). Based on these findings, UVA-1 was tested in SLE patients in varying dosing regimens in case report, open-label and randomized control trial settings ( Table 2) (37)(38)(39)(40)(41)(46)(47)(48)(49)(50). In these trials, UVA-1-treated patients demonstrated decreased systemic symptoms and disease activity scores (e.g.…”
Section: Uva-1 Therapy For Lupus Patientsmentioning
confidence: 99%
“…Solar UV-B photons isomerize UCA from its resting trans- form to the active cis- isomer, which suppresses CMI. Even the UV-B photons emitted from uncovered fluorescent lamps isomerize UCA to its active cis isomer 13 in vitro and increase disease activity in vivo . 66 Teleologically, the suppression of CMI may serve to protect against solar-mediated actinic changes that would predispose patients to immune-mediated rashes and pruritus with every sun exposure.…”
Section: Urocanic Acid (Uca)mentioning
confidence: 99%
“…Currently, the only patient with interstitial lung disease (ILD) and pulmonary hypertension (PH) who was treated with UV-A1 irradiation was a 36-year-old Caucasian woman with antinuclear antibody (ANA)/anti-Sjögren syndrome-related antigen A (SSA)-positive lupus for a duration of five years. 13 She had been taking 400 mg of hydroxychloroquine and 6 mg of methylprednisolone for the previous year, without a significant effect. Within weeks of starting triweekly full-body UV-A1 irradiation at 8 J/cm 2 , her symptoms of fatigue, malar rash, polyarthritis, mouth ulcers, and intermittent pleurisy abated.…”
Section: Pulmonary Disease In Slementioning
confidence: 99%
See 1 more Smart Citation
“…UVA, UVB, and UVC are divided based on wavelength (UVA = 400–320 nm; UVB = 320–280 nm; UVC = 280–100 nm), with shorter wavelengths associated with higher energy effects. In general the longer wavelengths, such as UVA, which has been shown to have therapeutic potential in SLE patients ( 7 9 ), penetrate more deeply in the skin, reaching the dermis, whereas UVB is absorbed almost entirely by the keratinocytes of the epidermis ( 10 ). UVC rarely reaches the skin as it is primarily absorbed by atmospheric ozone.…”
Section: Introductionmentioning
confidence: 99%